Screening of a new candidate coxsackievirus B1 vaccine strain based on its biological characteristics - Zhang, Ming; Xu, Danhan; Liu, Yuhan; Wang, Xiaohui; Xu, Lilan; Gao, Na; Feng, Changzeng; Guo, Wei; Ma, Shaohui (Frontiers in Microbiology, 2023)
Coxsackievirus B1 (CVB1) is one of the significant pathogens causing viral myocarditis, hand, foot, and mouth disease (HFMD), and aseptic meningitis, and it has been associated with type 1 diabetes (T1DM). No effective antiviral drugs against CVB1 infection or preventive vaccines are available. Thanks to the success of two inactivated vaccines against enterovirus 71 and poliovirus, an inactivated Vero cell-based CVB1 vaccine could be developed. In this study, we isolated a high-growth CVB1 virus strain KM7 in Vero cells and developed a Vero-adapted vaccine candidate strain KM7-X29 via three rounds of plaque purification and serial passages. The KM7-X29 strain was grouped into the GII subgenotype, which belonged to the Chinese epidemic strain and grew to a titre of more than 107 CCID50/ml in Vero cells. The inactivated CVB1 vaccine produced by the KM7-X29 strain induced an effective neutralizing antibody response in BALB/c mice and maternal antibodies were able to provide a 100% protective effect against lethal challenges with a CVB1 strain in suckling BALB/c mice. Thus, the KM7-X29 strain might be used as a new candidate coxsackievirus B1 vaccine strain. The neonatal murine model of CVB1 infection will contribute to the development of the CVB1 vaccine.